BUILDING SCHOOL CULTURE THROUGH IMPLEMENTATION OF CHARACTER EDUCATION - Alexander Ferdinan Tuati; Unifah Rosyidi; Siti Zulaikha (Fakultas Ekonomi Universitas Negeri Jakarta, 2019)
The purpose of this study is to examine school culture through character implementation. This study used a qualitative approach, research does not use calculations or termed scientific research that emphasizes the natural character of the data source. Amid changes in a globalized world that is very dynamic, schools must develop a positive culture to prepare millennial generations in science, technology, and character. The founding spirit in the vision and mission became the basis for the development of school culture. From year to year, there is always a change in the components of the school, there is a graduating class, and there are new classes, as well as teachers and education staff. These conditions make them unable to work in the same spirit and achieve school goals. The results of this research are the development of school culture in question is to build habits in applying school values ​​(religiosity, nationalist, independent, cooperation, integrity), running school rules, work habits to achieve school goals. Character education in the 2013 curriculum gives space for schools to build school culture through character education refraction and set an example.